The Story So Far: How Embodied Cognition Advances Our Understanding of Meaning-Making - Galetzka, Cedric (Frontiers in Psychology, 2017)
Meaning-making in the brain has become one of the most intensely discussed topics in cognitive science. Traditional theories on cognition that emphasize abstract symbol manipulations often face a dead end: The symbol grounding problem. The embodiment idea tries to overcome this barrier by assuming that the mind is grounded in sensorimotor experiences. A recent surge in behavioral and brain-imaging studies has therefore focused on the role of the motor cortex in language processing. Concrete, action-related words have received convincing evidence to rely on sensorimotor activation. Abstract concepts, however, still pose a distinct challenge for embodied theories on cognition. Fully embodied abstraction mechanisms were formulated but sensorimotor activation alone seems unlikely to close the explanatory gap. In this respect, the idea of integration areas, such as convergence zones or the ‘hub and spoke’ model, do not only appear like the most promising candidates to account for the discrepancies between concrete and abstract concepts but could also help to unite the field of cognitive science again. The current review identifies milestones in cognitive science research and recent achievements that highlight fundamental challenges, key questions and directions for future research.